Evaluation of conditioning temperature and retention time on Enterococcus faecium inactivation, vitamin stability, metabolizable energy, and amino acid digestibility - J.I. Vargas; W.J. Pacheco; L.M. Almeida; C.W. Starkey; E. Monu (Journal of Applied Poultry Research)
Summary: Salmonella is a pathogen that can enter the poultry supply chain if feed is manufactured using contaminated ingredients. Hygienisers have emerged as a viable strategy for reducing pathogen levels by extending the retention time of feed during conditioning. The objective of this study was to evaluate the effects of conditioning temperature (75, 85, and 95°C) and retention time (15, 95, 175, and 255 s) on the inactivation of feed Salmonella surrogate Enterococcus faecium (E. faecium) and vitamin stability in Experiment 1, and true metabolizable energy corrected to nitrogen equilibrium (TMEn) and true amino acid digestibility (TAAD) in Experiment 2. In Experiment 2, fifty cecectomized roosters were fasted for 30 h before being precision-fed 35 g of a control mash diet without thermal processing, or feed conditioned at 75°C for 95 s, 85°C for 175 s, and 95°C for 255 s. E. faecium levels decreased at all conditioning temperatures and retention times, with the highest reductions at conditioning temperatures of 85 and 95°C with retention times of 15, 95, 175, and 255 s (> 5-log CFU/g). The stability of fat-soluble vitamins decreased as retention time increased. In contrast, water-soluble vitamins were stable under varying conditioning temperatures and retention times. Diets conditioned at 75°C and retained for 95 s had 81 kcal/kg higher TMEn compared to the control mash diet. Conditioning temperature and retention time did not influence TAAD. Overall, the manipulation of conditioning temperature and retention time can be a viable strategy to mitigate microbial load in feed and increase TMEn, without negatively affecting AA digestibility and water-soluble vitamin stability.